Economical Considerations on CCS System for Geological Uncertainty and Injection Failure - Suzuki, Haruhiro; Yousefi-Sahzabi, Amin; Sugai, Yuichi; Yousefi, Hossein; Sasaki, Kyuro (International Journal of Energy Economics and Policy, 2014)
In this study, an operation research on the performances of Tomakomai CCS project has been carried out for investigating the permeability uncertainty and the failures on CO2 operation and transportation. Firstly, economical effects of estimation error in aquifer permeability were investigated by using a reservoir block modeling based on numerical simulation results on CO2 injection rate. Secondary, economic loss resulted from failure of CO2 injection was evaluated by assuming periodical injection halts. It is clear that CO2 buffers, such as sphere gas tanks, should be installed to store CO2 on the CCS process which can temporarily store CO2 after it is captured when a trouble on transportation or injection processes occurs. Without a buffer, releasing the captured CO2 to the atmosphere due to system failure or trouble in injection will add to capture costs, or will result in carbon tax or opportunity loss on CCS. The larger size of CO2 buffer volume can potentially withstand against long-term trouble, however the larger buffer volume needs larger cost for initial construction and maintenance. The study also present the optimum CO2 buffer volume based on economical evaluations for a commercial CCS model based on several simulations performed with and without CO2 buffer in the system. Keywords: CCS; Uncertainty; Economic Evaluations; Permeability; CO2 Buffer JEL Classifications: Q35; Q41; Q55